Information needs and seeking behaviour of lawyers. - Manoj, P. (2008)
This study was conducted to determine the information needs and seeking behaviour of litigation lawyers. The purpose was to investigate the types of information sources and the preferences of lawyers in selecting different information sources. It also investigates the different types of information required at various stages of a case and tries to understand the adequacy of information to the lawyers.